Chapter 1 Housing careers, intergenerational support and family relations - Ronald , Richard (Taylor & Francis, 2019)
The home and family have always been mutually embedded, with the former central to the realization and reproduction of the latter. More recently, this mutuality has taken on a more critical salience as realignments in housing markets, employment and welfare states in many countries have worked together to undermine housing access for new households. In this context, families have become increasingly involved in smoothening the routes of young adults members up the 'housing ladder' into home ownership. Intergenerational support appears to have become much more widespread and not just confi ned to familialistic welfare regimes. The role of intergenerational support for housing remains, however, highly diff erentiated across countries, cities and regions, as well as uneven between social and income classes. This introduction to the Special Issue explores how the role of housing wealth transfers has impacted the renegotiation of the generational contract. In doing so, it sets the scene for the articles that follow, each of which contribute signifi cantly to advancing understanding of housing as a key driver of contemporary social relations and inequalities.